Detection of formaldehyde vapor using glass substrate coated with zinc oxide nanorods - Yasin, Mohammad; Mohd Yusof, Haziezol Helmi; Jali, Mohd Hafiz; Md Johari, Md Ashadi; Dimyati, Kaharudin; Harun, Sulaiman Wadi; Khasanah, Miratul (Institute of Electrical and Electronics Engineers Inc., 2019)
A glass substrate coated with ZnO nanorods via a hydrothermal method for formaldehyde vapor sensing is reported. The proposed sensor device was characterized against formaldehyde vapor concentrations varying from 1% to 5% with a reference point as 0% (pure water) at room temperature. A significant sensing response was observed where the output voltage reduced by 0.0856 V via scattering effect by ZnO nanorods upon exposure to the maximum tested concentration (5%). The sensitivity and linearity of the sensing response were recorded to be approximate values of -0.0168 V/% and 98.06% correspondingly. The sensor device was found to have good measurement stability in measuring as low as 1% of concentration for a prolonged time of 600 s. This proposed sensor has potential applications in monitoring air pollution caused not only by formaldehyde vapor but also by other harmful and toxic vapors or gases.